Transparent carbon nanosheet from polyethylene using E-beam pre-treatment - Choi, Dalsu; Lee, Sungho (ELSEVIER SCIENCE BV, 2019)
We present an electron beam (E-beam) pre-treatment technique as a mean to crosslink polyethylene (PE) thin film for fabricating carbon nanosheets (CNSs) with improved transparency. In a previous study, we demonstrated successful conversion of innately non-carbonizable PE into transparent CNSs through thermal oxidative stabilization. Unlike other studies about CNSs fabrication using pricey precursors, PE has strong merits because it is the cheapest and the most abundantly used plastic. However, transparency and uniformity of CNSs from PE were not desirable as transparent electrode. Here, by adopting E-beam irradiation as a pre-treatment process before thermal stabilization, we could enhance the transparency and electrical property of PE derived CNSs so that they can be effectively utilized as transparent conducting electrode. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: WASTE